Inventing a saga form: The development of the kings’ sagas - Armann Jacobsson (Filologia Germanica, 2024)
This study concerns form and the aesthetics of the Kings’ Sagas, a subject that has been somewhat neglected by previous kings’ saga scholars. Among the formal categories that will be given particular attention are the role of anecdotal material and skaldic verse within the framework of a larger saga. Five texts usually categorised as kings’ sagas will receive particular attention. The article aims at highlighting important concerns for further study of the aesthetics and form of the kings’ sagas, using the texts to demonstrate the development and the variation.